2010
DOI: 10.1007/s00038-010-0131-x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and anticipated attitudes of the community about bird flu outbreak in Turkey, 2007–2008: a survey-based descriptive study

Abstract: Preparedness against bird flu endemic in remote regions could be hindered by factors, such as low levels of education and economic dependence on small-scale backyard farming. The baseline data collected in this survey will be useful in monitoring changes over time in the population's perceptions of threat, and its attitude towards compliance with specific public health recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…While these prior studies also identified knowledge of AI, such as modes of AI transmission, to be a significant factor for increased preventive behavior, our study discovered that to promote the recommended AI preventive behavior, it is crucial to inform the public specifically of the AI fatality rate. In addition, unlike most previous research [18][19][20] which focused on poultry workers or the general public, this study expanded this line of research by examining AI preventive behavior and related factors among traditional market workers and shoppers.…”
Section: Knowledge Of Ai Fatality Rate and Risk Perceptionmentioning
confidence: 99%
See 2 more Smart Citations
“…While these prior studies also identified knowledge of AI, such as modes of AI transmission, to be a significant factor for increased preventive behavior, our study discovered that to promote the recommended AI preventive behavior, it is crucial to inform the public specifically of the AI fatality rate. In addition, unlike most previous research [18][19][20] which focused on poultry workers or the general public, this study expanded this line of research by examining AI preventive behavior and related factors among traditional market workers and shoppers.…”
Section: Knowledge Of Ai Fatality Rate and Risk Perceptionmentioning
confidence: 99%
“…Similarly, in a limited number of AI studies which included gender as a variable, its effect on the AI preventive behavior was generally found to be not statistically significant [e.g., 19,26]. On the other hand, higher education levels have repeatedly been reported to be associated with increased knowledge and intention to adopt the recommended AI preventive behavior [e.g., 18,19,26]. Consistent with these findings, our study also found participants with higher education levels to be more likely to practice the AI preventive behavior.…”
Section: Interactive Effect Between Gender and Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the first steps to increase the level of public health information, media play an effective role to spread the basic knowledge concerning prevention and transmission of such diseases. This might be the most effective way of training in pre-college education (1,10,14,15). This study was a complement for our previous study.…”
Section: Discussionmentioning
confidence: 60%
“…In general, numerous LPMs are widely distributed in urban areas that might facilitate avian-to-human and subsequent human-to-human transmissions of novel influenza viruses, unlike poultry farms, which are more frequently located in rural areas. Such geographical differences between the urban and rural areas affected the awareness of AI in Turkey [ 37 ] and in China [ 38 ]. In the past, closure of LPMs has been implemented after the confirmation of severe or fatal human cases of H5N1 and H7N9 [ 39 ].…”
Section: Discussionmentioning
confidence: 99%